Pengaruh Rating dan Ulasan Google Maps terhadap Brand Loyalty yang di Mediasi Customer Trust pada Dua Tempat Makan di Surakarta - Burhan Permata; Moechammad Nasir (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the influence of Google Maps ratings and reviews on brand loyalty, with customer trust as a mediating variable, in the context of two well-known restaurants in Surakarta: Dapur Solo and Mang Engking. The rapid growth of digital platforms has significantly transformed consumer decision-making in the culinary industry, where online ratings and user-generated reviews serve as important sources of information. This research adopts an explanatory quantitative approach and employs Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze data collected from 400 respondents who have visited the selected restaurants and interacted with Google Maps ratings and reviews. The results reveal that Google Maps ratings and reviews have a positive and significant effect on customer trust in both restaurants. However, the effect is stronger for Dapur Solo, where trust plays a more prominent role in enhancing brand loyalty, compared to Mang Engking. Similarly, while ratings and reviews influence brand loyalty directly in both cases, the indirect effect through customer trust is more pronounced for Dapur Solo. These findings highlight that customer trust functions as a crucial psychological mechanism strengthening the relationship between digital information cues and long-term customer loyalty, with varying impact across different restaurant brands. This study contributes to marketing literature by providing empirical evidence on the role of Google Maps as an effective digital marketing tool in the local culinary industry. Practically, the findings suggest that restaurant managers should actively manage online ratings and reviews to enhance customer trust and foster sustainable brand loyalty, especially considering brand-specific differences in consumer responses.